Lentilactobacillus buchneri domination during the fermentation of Japanese traditional fermented fish (funazushi). Issue 11 (27th July 2022) - Tanabe, Koichi; Monguchi, Masaki; Inoue, Ryoga; Zamami, Rio; Nakanishi, Ryo; Manabe, Ayano; Oe, Kaho; Komatsuzaki, Noriko; Shima, Jun
Abstract: Funazushi is a Japanese traditional fermented fish made with boiled rice without the addition of microbial starter cultures. Isolates from various commercial funazushi products, as identified by 16S rDNA sequences, suggested that Lentilactobacillus buchneri strains are major lactic acid bacteria. Based on an analysis of the putative CRISPR (clustered regularly interspaced short palindromic repeat) region, the genetic diversity of L. buchneri strains was examined. The data suggested that the diversity of L. buchneri strains depended on the factories at which funazushi was produced. An analysis of samples during fermentation indicated that the transition of microbes occurred, and L. buchneri was the dominant species. To determine the factors associated with domination, bacteriocin production and environmental stress tolerance, including NaCl and organic acid (lactate and acetate) tolerance, were evaluated. L. buchneri isolates did not produce bacteriocin. Although the isolates did not exhibit NaCl tolerance, they displayed higher lactate tolerance than other lactic acid bacteria isolated during funazushi fermentation. Based on reports that L. buchneri can convert lactate to acetate, the previous and present results suggested that lactate tolerance and lactate conversion in L. buchneri could explain its domination in funazushi. Our study presented a model for the domination mechanisms of specific microbes in fermented foods by spontaneous fermentation. Abstract : This study investigated the major lactic acid bacteria in funazushi, Japanese traditional fermented fish made with boiled rice without the addition of microbial starter cultures. An analysis of samples during fermentation of funazushi indicated that the transition of microbes occurred, and Lentilactobacillus buchneri became the dominant species. The tolerance to lactate in L. buchneri could explain its domination in the fermented food.